2022 Malaysian Working Group Consensus Statement on Renal Denervation for management of arterial hypertension - Chia, Yook Chin *; Wan Azman, Wan Ahmad; Fong, Alan Yean Yip; Azhari, Rosman; Abdul Rashid, Abdul Rahman; Choo, Gim Hooi; Lim, Soo Kun; Mohammad Zawawi, Abu Bakar; Ong, Tiong Kiam (Sprinter Nature, 2022)
Hypertension is highly prevalent and a major contributor to cardiovascular mortality and morbidity. In spite of the availability of efficacious, safe and affordable anti-hypertensive drugs, hypertension remains poorly controlled in the majority of hypertensive patients. Various reasons including non-adherence to the anti-hypertensive drugs, account for the poor control. Resistant hypertension is also one of the reasons for poor control of blood pressure (BP). The sympathetic nervous system (SNS) has long been recognized as one of the determinants in the pathophysiology of a raised BP. Overactivity of the SNS is a contributor to sustained arterial hypertension. Renal denervation (RDN) is increasingly recognized as a safe and effective adjunctive therapy to control BP with or without pharmacotherapy. Hence for patients who remain uncontrolled despite all efforts, renal denervation (RDN) is a novel treatment that can potentially improve BP control, hence reducing the major adverse cardiovascular events (MACE). More recent randomized, sham control trials of RDN have shown that RDN produces a sustained lowering of BP. To date, this lowering of BP through RDN is maintained for at least 3 years. Furthermore, this procedure has been found to be safe. Hence this consensus summarises the science behind RDN and the available clinical data to support the use of this therapy. It is hoped that this consensus will offer guidance on the importance of identifying patients who will benefit most from this therapy. A multidisciplinary team approach in the management of the patient undergoing RDN is recommended.